Natural dye‐sensitized solar cells: Case study with tropical organic pigments. Issue 4 (28th January 2021) - Pereira, José Waltrudes Castanheira; Cataldi, Marcio; Salcedo, Ivanovich Lache
Abstract: In recent years, the increase in evolution of new photovoltaic technologies demonstrates the global importance given to solar energy. New photovoltaic technologies are in the third generation. The article presents a third‐generation technology of solar cells called dye‐sensitized solar cell (DSSC), enhancing cell efficiency through material improvements. DSSC is a solar technology with minimal environmental impact and low cost in manufacturing. The dyes used in the study were natural dyes of açaí and chlorophyll. For better electrical comprehension of natural dye‐sensitized solar cells, the cells were tested with varying temperature and irradiance. The main objectives were to introduce and improve sensitized solar cells with the combination of a Brazilian dye ( açaí ) with a global dye (chlorophyll), indicating a potential renewable source to South America.